2022
DOI: 10.3390/ijerph19137677
|View full text |Cite
|
Sign up to set email alerts
|

Using Open-Access Data to Explore Relations between Urban Landscapes and Diarrhoeal Diseases in Côte d’Ivoire

Abstract: Unlike water and sanitation infrastructures or socio-economic indicators, landscape features are seldomly considered as predictors of diarrhoea. In contexts of rapid urbanisation and changes in the physical environment, urban planners and public health managers could benefit from a deeper understanding of the relationship between landscape patterns and health outcomes. We conducted an ecological analysis based on a large ensemble of open-access data to identify specific landscape features associated with diarr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
2
3
0
Order By: Relevance
“…Construction materials and the spatial disposition of cooking spaces were consistently associated with higher risks of diarrhea, even accounting for access to basic sanitation and hygiene amenities, continuity of water services, and socioeconomic status. These results corroborate previous findings regarding spatial predictors of diarrhea in Côte d’Ivoire [ 17 ], suggesting that housing conditions may play an important role in mediating contamination pathways that cause diarrhea.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Construction materials and the spatial disposition of cooking spaces were consistently associated with higher risks of diarrhea, even accounting for access to basic sanitation and hygiene amenities, continuity of water services, and socioeconomic status. These results corroborate previous findings regarding spatial predictors of diarrhea in Côte d’Ivoire [ 17 ], suggesting that housing conditions may play an important role in mediating contamination pathways that cause diarrhea.…”
Section: Discussionsupporting
confidence: 91%
“…Building on our recent research [ 17 , 18 ] and on previous environmental health studies in SSA [ 9 , 13 ], this study argues for a holistic approach to the prevention of diarrheal diseases that, beyond WASH services, also addresses the physical environment and the spatial characteristics of poverty [ 19 ]. Our starting point was the assumption that inadequate dwelling conditions hamper the potential health benefits expected from WASH interventions, which can be indirectly measured by the risk of diarrhea [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are aspects related to the specific settlement’s morphology that are associated with the perceived safety in accessing those facilities, and this may have significant health implications. These findings resonate with a recent ecological study conducted in Côte d’Ivoire, which showed that specific landscape features related to dense, deprived settlements were a more accurate predictor of diarrhea in Ivorian urban areas than the sole availability of sanitation services [ 62 ]. In fact, although the availability of sanitation services represents a theoretical improvement, in practice, the health benefits of these improved services may be null if the targeted populations do not feel safe to use them.…”
Section: Discussionsupporting
confidence: 88%
“…The latter remain amongst the main causes of death worldwide, especially in Africa (GBD 2018;Diarrhoeal Disease Collaborators, 2018), and can be used as a proxy indicator of the quality of access to WASH services (Clasen et al, 2014). The study uses readily available open access data and combines quantitative spatial analyses conducted at different geographic scales, and thus relies on ecological analyses at city scale and cross-sectional household surveys at neighbourhood scale (Pessoa Colombo et al, 2022).…”
Section: Healthcare Systems and Innovationsmentioning
confidence: 99%